The Mockumentary: History of a Deception. Perception, Image Consciousness, and Narrative Engagement (Itinera, 2024)
This article aims to investigate the documentary film image through the lens of phenomenological image theory. Specifically, it seeks to explore the genre of mockumentary, reflecting on the reasons behind the deception that lead the consciousness to believe that what it is seeing has really happened. In the phenomenological literature, the theme of deception has often been addressed through the case of hyperrealistic wax statues, which exemplify the typical perceptual misunderstanding of mistaking an image for a flesh-and-blood person. In contrast to the wax figures model, I argue that there is no perceptual deception in mockumentaries. On the contrary: mockumentaries work precisely because they do not attempt to deceive perception. Rather, the idea I propose is to interpret the deception of the mockumentary in terms of a narrative engagement of perception.
Keywords: mockumentary, perception, image consciousness, deception, narrative engagement